Knowledge of Prospective Mathematics Teachers About Preparation Lesson Plans in the Curriculum 2013 - Yeni Fitri; Hayatun Nupus (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
Improving the quality of learning for candidates of prospective mathematics teachers is needed, so prospective educators can improve the quality of learning and education in Indonesia. Moreover, PPL students (Field Experience Program) is still very minimal knowledge about curriculum 2013. This research aims to describe the knowledge of prospective mathematics teachers in the preparation of a Lesson Plan (RPP) in the curriculum 2013. Techniques used in data collection include (1) documentation in the form of a collection of lesson plans (RPP) and (2) structured interviews. The knowledge of mathematics teacher candidates about the curriculum 2013 in the preparation of RPP, shows that Subject 2 is higher than Subject 1. Subject 1 with an average of 3.45, and Subject 2 with 3.57. The results of the analysis of the assessment conducted show that the knowledge of mathematics teacher candidates about the Curriculum 2013 is very good, there are still some inaccurate understandings, such as knowledge of the relationship between curriculum tools, compatibility of KD and components in RPP, sources and media to learn knowledge about the context in preparation of perceptions and motivation and the link between learning activities and learning models.